Curled Flag Leaf 2, Encoding a Cytochrome P450 Protein, Regulated by the Transcription Factor Roc5, Influences Flag Leaf Development in Rice - Zhang, Xiaobo; Wang, Ying; Zhu, Xiaoyan; Wang, Xiaowen; Zhu, Zhu; Li, Yangyang; Xie, Jia; Xiong, Yuzhen; Yang, Zhenglin; He, Guanghua; Sang, Xianchun (Frontiers in Plant Science, 2021)
Moderate curling generally causes upright leaf blades, which favors the establishment of ideal plant architecture and increases the photosynthetic efficiency of the population, both of which are desirable traits for super hybrid rice (Oryza sativa L.). In this study, we identified a novel curled-leaf mutant, curled flag leaf 2 (cfl2), which shows specific curling at the base of the flag leaf owing to abnormal epidermal development, caused by enlarged bulliform cells and increased number of papillae with the disordered distribution. Map-based cloning reveals that CFL2 encodes a cytochrome P450 protein and corresponds to the previously reported OsCYP96B4. CFL2 was expressed in all analyzed tissues with differential abundance and was downregulated in the clf1 mutant (a mutant harbors a mutation in the HD-ZIP IV transcription factor Roc5). Yeast one-hybrid and transient expression assays confirm that Roc5 could directly bind to the cis-element L1 box in the promoter of CFL2 before activating CFL2 expression. RNA sequencing reveals that genes associated with cellulose biosynthesis and cell-wall-related processes were significantly upregulated in the cfl2 mutant. The components of cell wall, such as lignin, cellulose, and some kinds of monosaccharide, were altered dramatically in the cfl2 mutant when compared with WT. Taken together, CFL2, as a target gene of Roc5, plays an important role in the regulation of flag leaf shape by influencing epidermis and cell wall development.